The classical dancer’s experience in a pas de deux with pain (Research, Society and Development, 2023)
The present study aims to answer the following argument: what is the dancer's relationship with pain, and until when can pain be an ally or a major boost for the recurrence of injuries and traumas in classical dancers? The research is of a descriptive nature, describing the experience and characteristics of the reality of dancers in relation to pain, with a quali-quantitative approach, primary because at the end of this study a sample of data and conclusions on the subject was carried out, and it is also transverse. The research was carried out via Google forms, carried out with male and female dancers aged between 18-40 years who have been practicing ballet for a period of time ≥ 5 years. Mostly 53.6% consider Ballet their profession, 39.3% of participants practice the modality for about 10 hours a week. They report that the life of a Ballet practitioner is intense, with too many charges but immensely satisfying. Ballet's impact on their lives was perceived both positively and negatively. Given the above, it was possible to understand how dancers deal with pain, through neural modulations of opioid and dopaminergic systems. In addition, it was possible to observe that emotional stress is associated with injuries acquired within the practice of classical ballet. There was a significant role for physiotherapy in the prevention and treatment of injury and trauma in classical dancers.